1991
DOI: 10.1177/001872089103300602
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Behavior, Workload, and Performance in Task Scheduling

Abstract: Scheduling theory is proposed as a normative model for strategic behavior when operators are confronted by several tasks, all of which should be completed within a fixed time span, and when they are free to choose the order in which the tasks should be done. Three experiments are described to investigate the effect of knowing the correct scheduling rule on the efficiency of performance, subjective workload, and choice of strategy under different conditions of time pressure. The most potent effects are from tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 7 publications
1
48
0
Order By: Relevance
“…Taking into consideration a study by Moray, Dessouky, Kijowski, and Adapathya (1991), algorithm comprehensibility could also imply a very high cognitive workload. Then, as cognitive resources are limited, schedulers could invest fewer cognitive resources in the rescheduling task than when the algorithm is not comprehensible.…”
Section: Algorithm Comprehensibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Taking into consideration a study by Moray, Dessouky, Kijowski, and Adapathya (1991), algorithm comprehensibility could also imply a very high cognitive workload. Then, as cognitive resources are limited, schedulers could invest fewer cognitive resources in the rescheduling task than when the algorithm is not comprehensible.…”
Section: Algorithm Comprehensibilitymentioning
confidence: 99%
“…To identify complacent behavior it is necessary to compare performances with a standard; in other words, the best performance that operators can achieve. In scheduling, Moray et al (1991) demonstrated that, from a mathematical point of view, humans are not able to attain optimal performance. For this reason, algorithms are compared in pairs, one having a characteristic that could lead to complacent behavior and the other able to determine the maximum human-performance obtainable.…”
Section: Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…De Keyser, 1995). For instance, Moray et al (1991), using Tulga and Sheridan's (1980) experimental paradigm, found evidence that operators faced with various tasks of different duration prefer to start the longest task first, even though the normative model would require the shortest task to be started first. In a multi-task micro world experiment (combined manual and supervisory control), Kirlik (1993) found evidence that operators are sensitive to the temporal costs of automation and refuse to use an automatic aid if its engagement is associated with a considerable delay.…”
Section: Representation Analyis and Design Of Dynamic Function Schedmentioning
confidence: 99%